Instrumen Kebajikan ke Arah Komitmen Terhadap Organisasi : Satu Kajian di Batalion Kesembilan Rejimen Renjer DiRaja - Gulam Rasul, Abdus Subhan (2004)

(untitled)
This research was carried out to find out the level of organizational commitment among the officers and staff from 9 Royal Ranger (9 RRD) of the Army-The study was twofold. Firstly, it sought to determine the association between welfare given by the Armed Forces and unit 9 RRD in relation to organizational commitment. Secondly, the study was also to find out the differences between commitment toward organizational and demography based on age, academic, services,marital status,rank and wages. Questionaires with a total of 37 questions were used as a research instrument. Respondents total of 112 comprising of officers and other rank were randomly selected. The data collected were analyzed using the Statistical Package for Social Science (SPSS) Versi 11.0 software programme. Statistical analysis techniques such as Pearson Correlation test, t-Test and ANOVA were used to test the 9 hypotheses. The findings revealed positive and significant relationship between welfare given by the Armed Forces and unit 9 RRD in relation to organizational commitment. The finding based on descriptive measure of commitment towards organizational and demography shown that there are relation and significant on the bases of age and pay. Others such as academic, services, marital status and rank shown that there were not significant. Based on this study, implications fiom the finding were highlighted to the Infantry Directorate of the Army as an effort in enhancing commitment towards organizational of the Armed Forces and 9 RRD.